Hybrid Power Generation System to Promote New Energy Consumption - Kun YANG; Lei SUN; Chaoyun FANG; Yi ZHANG (Zhongguo dianli)
Solar power is increasing day by day, and the scheduling and controllability of the previous single photovoltaic power generation system running on the grid are insufficient. A new hybrid power generation system is proposed to improve the sensitivity of scheduling. The system includes wind farms, photovoltaic power plants, solar thermal power plants and electric heaters. The electric heater is mainly to convert the excess wind and light energy into heat energy and store it in the heat storage tank of the solar power plant. By using the good scheduling and controllability of the heat storage thermal power station, it improves the rotating reserve and climbing capacity of the system, reduces the randomness and uncertainty of the scenery output, so as to improve the consumption of new energy. In order to maximize the net income of the system, the model is established to maximize the system profit under technical constraints, and the influence of the hybrid power generation system on the new energy consumption under different climate conditions is studied.